Properties of ion beams generated by nitrogen plasma focus - Akel, M.; Alsheikh Salo, S.; Saw, S. H.; Lee, S. (Springer US, 2014)
Numerical experiments have been systematically carried out using the modified Lee model code on various plasma focus devices operated with nitrogen gas. The ion beam properties (ion beam energy, ion beam flux, ion beam fluence, beam ion number, ion beam current, power flow density, and damage factor) of the plasma focus have been studied versus gas pressure for each plasma focus device. The results show that, for these studied plasma focus devices, the mean ion energies decrease with increasing gas pressure, while the beam ion number increases with higher pressure. The fluence, flux, ion current, power flow density and damage factor have maximum values at the optimum pressure. It is shown that, the maximum power flow densities range from 1012 to 1014 W m−2 and the damage factor values reach almost 109–1011 W m−2 s0.5. The obtained results provide much needed benchmark reference values and scaling trends for ion beams of a plasma focus operated in nitrogen gas. These results could be used as an indicator for ion properties emitted from nitrogen plasma focus for various applications including material processing.